Natural course of tricuspid regurgitation and prognostic implications - Peter Bramlage; Maki Okamoto; Christian Butter; Karin Bramlage; Marwin Bannehr; Christoph Roland Edlinger; Ulrike Kahn; Josephin Liebchen; Valentin Hähnel; Victoria Dworok; Fabian Schipmann; Tanja Kücken; et al. (Open Heart)
Objective Functional tricuspid regurgitation (TR) is a frequent finding in echocardiography. Literature suggests significant TR is associated with poor prognosis. Still, data remain limited. This study aimed to evaluate long-term prognostic implications in patients with TR.Methods In this observational cohort study, data from 1650 consecutive patients were analysed. Primary endpoint was all-cause mortality. Mean follow-up time was 1090 days. TR grades at baseline and follow-up were compared. Survival analyses were performed to identify prognostic factors.Results At baseline, 14.1% patients showed no, 63.8% mild, 17.4% moderate and 4.7% severe TR. 359 patients (21.8%) died within the study period. TR at baseline was associated with excess mortality. Moderate and severe TR were of prognostic implication in all subgroups irrespective of systolic pulmonary artery pressure (sPAP) (</≥40 mm Hg) and left ventricular ejection fraction (LV-EF) (</≥50%). Survival was worst in patients with moderate and severe TR and concomitant elevated sPAP or reduced LV-EF at 1 and 3 years, respectively (p<0.001; p<0.001). In a multivariate model, including cardiac and non-cardiac risk factors, moderate and severe TR, sPAP and impaired right ventricular (RV) function were independent predictors for survival (HR 1.89, CI 1.07 to 3.36, p=0.029; HR 2.93, CI 1.57 to 5.49, p=0.001; HR 1.44, CI 1.25 to 1.65, p<0.001; HR 1.43, CI 1.14 to 1.79, p=0.002). Overall progression of TR on follow-up was 28.4%. Patients with TR progression showed significantly worse survival (HR 1.44, CI 1.11 to 1.81; p=0.006).Conclusion While TR progressed over time, it was associated with impaired long-term survival. TR grade, RV dysfunction, sPAP and TR progression were independent predictors for survival.